Efficacy of acupuncture therapy plus related rehabilitation therapy for post-stroke urinary incontinence: a systematic review and meta-analysis - Dai, Zifeng; Wang, Yuting; Du, Yuzheng; Hou, Linru; Li, Yufen; Ma, Kaixuan; Yan, Qinfeng; Wen, Jian; Dong, Xinlei; Chen, Xiaolin; Zhang, Lili (Frontiers in Neurology, 2025)
IntroductionResearchers have increasingly focused on the efficacy of acupuncture therapy (AT) combine with rehabilitation therapy (RT) for post-stroke urinary incontinence (PSUI). This study aims to fully assess the efficacy of AT plus related RT in treating PSUI.MethodsWe systematically searched eight databases from their inception to March 2025 for randomized controlled trials (RCTs) evaluating AT plus related RT for PSUI. Stata 18.0 was utilized for the meta-analyses.ResultsThirty-six studies involving 2,796 subjects were included, with AT plus related RT performed in the treatment group. The total effective rate of AT plus RT was significantly higher than that of RT or AT alone [RR = 1.23, 95% CI (1.19, 1.28), p < 0.001]. AT plus RT was also superior to related RT or related AT in improving maximum bladder capacity [WMD = 44.93, 95% CI (32.00, 57.87), p < 0.001]; increasing maximum urinary flow rate [WMD = 2.64, 95% CI (1.27, 4.01), p < 0.001], mean urine output per time [WMD = 44.30, 95% CI (20.31, 68.29), p < 0.001], and pelvic floor muscle strength (including fast [WMD = 2.64, 95% CI (1.04, 4.25), p = 0.001], slow [WMD = 6.09, 95% CI (3.44, 8.75), p < 0.001], and complex muscle fibers [WMD = 5.46, 95% CI (3.60, 7.32), p < 0.001]); and reducing the residual urine volume [WMD = −20.84, 95% CI (−27.53, −14.14), p = 0.001], maximal detrusor pressure [WMD = −10.6, 95% CI (−12.72, −8.55), p = 0.001], frequency of 24-h UI [WMD = −1.40, 95% CI (−1.92, −0.88), p < 0.001], and frequency of 24-h urination [WMD = −3.76, 95% CI (−4.87, −2.66), p < 0.001]. Moreover, AT plus RT significantly reduced scores on the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) [WMD = −2.40, 95% CI (−2.93, −1.83), p < 0.001]. While reductions were also observed in the quality of life (QOL) score [WMD = −0.72, 95% CI (−1.64, 0.20), p = 0.127] and the National Institutes of Health Stroke Scale (NIHSS) score [WMD = −3.51, 95% CI (−8.20, 1.18), p = 0.143], these did not reach statistical significance. Additionally, AT plus RT significantly increased the Incontinence Quality of Life Scale (I-QOL) score [WMD = 11.71, 95% CI (8.10, 15.33), p < 0.001] and the Barthel index (BI) score [WMD = 6.92, 95% CI (−0.22, 14.05), p = 0.058].DiscussionAT plus RT outperforms related RT or related AT in improving clinical efficacy and bladder function in PSUI patients. However, the number of included studies on AT plus RT remains limited, highlighting the need for more high-quality RCTs are needed to validate the findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier [CRD42024588520].